Contextualization of IsiXhosa Language Speech Acts Through Art Practice - Mpako, Nombeko P (Cultural Arts Research and Development, 2024)
This article represents an iconographic analysis of a selection of artworks from the author’s recent solo exhibition entitled Obu bubomi bam 8 out of 8: I teach Art, 2021. The selected artworks were titled using isiXhosa language speech acts which complement their visual narratives and expand their iconographic meanings. IsiXhosa is one of South Africa’s indigenous languages and is also the author’s mother tongue. The titles were consciously constructed to contribute to the art activism inherent within the artworks. These artworks do not only tell an authentic life story, they also highlight the importance of language in extending the impact of the visual narratives so that they are accessible to all viewers. This is because for any information and or message to be understood and meaningful to another person it must be conveyed through everyday / vernacular language. Thus, the selected artworks presented in this article were meant to influence and engage the viewers meaningfully as art actionism. The main objective of this article is to unpack these visual metaphors by reinterpreting the essence of their individual titles. The article is also meant to contribute to the contextualization of African indigenous languages as legitimate tools for the dissemination of inclusive and valuable knowledge.